Anesthetic considerations in Leigh disease: Case report and literature review - Terkawi, Abdullah Sulieman (Medknow Publications & Media Pvt Ltd, 2012)
Leigh disease is an extremely rare disorder, characterized by a progressive neurodegenerative course, with subacute necrotizing encephalomyelopathy. It usually presents in infancy with developmental delay, seizures, dysarthria, and ataxia. These patients may also develop episodes of lactic acidosis that usually lead to respiratory failure and death. Due to the rarity of the condition, the most appropriate anesthetic plan remains unclear. We present a patient with Leigh disease, who required general anesthesia. The pathogenesis of the disease is discussed and previous reports of perioperative care from the literature are reviewed.